2019
DOI: 10.1103/physreva.100.043822
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of partially coherent radiation by non-Hermitian localized structures having parity-time symmetry

Abstract: A theoretical model based on two point scatterers is suggested to investigate for the first time scattering of partially coherent radiation by a non-Hermitian localized structure, invariant under the simultaneous symmetry operations of parity inversion and time reversal. Within the first-order Born approximation, and the formalism of classical coherence theory, the spectral density of the scattered field in the far-zone is obtained analytically. We find that the unidirectional character of the scattered radiat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Various aspects of stochastic light scattering from deterministic PT -symmetric media were recently discussed in Refs. [16], [17] and [18]. The results of these studies can be deduced from the general theory developed here in the completely correlated medium limit.…”
Section: Introductionmentioning
confidence: 61%
“…Various aspects of stochastic light scattering from deterministic PT -symmetric media were recently discussed in Refs. [16], [17] and [18]. The results of these studies can be deduced from the general theory developed here in the completely correlated medium limit.…”
Section: Introductionmentioning
confidence: 61%
“…The scattering of partially coherent radiation caused by non-Hermitian structures, such as those for which PT symmetry is not conserved, with coherent systems is studied in [76].…”
Section: Discussionmentioning
confidence: 99%
“…The systems described in [76], i.e., which do not conserve PT symmetry, can also be affected by spectral singularities [38].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the scattering of partially coherent light by a deterministic medium with parity-time (PT) symmetric scattering potential has been studied [54]. The notion of PT symmetry is initially proposed in quantum mechanics that generalizes the real Hermitian systems into the complex domain [55,56].…”
Section: Introductionmentioning
confidence: 99%
“…The PT symmetry in optics has found numerous applications, such as in unidirectional invisibility, anisotropic transmission resonances, single-particle detection, microlaser, robust wireless power transfer, and topological insulators [58,59]. The partially coherent Gaussian Schell-model beam scattered by the PT deterministic media, such as the two-point scatterers [54,[60][61][62], localized continuous materials [63], and periodic materials with loss and gain [64] have been studied. It has been shown that the non-Hermitian property of the scattering potential induces anomalous spectral and spatial changes in the partially coherent scattered fields.…”
Section: Introductionmentioning
confidence: 99%